2014
DOI: 10.1038/onc.2014.57
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genomic and functional analyses reveal glyoxalase I as a novel metabolic oncogene in human gastric cancer

Abstract: Chromosomal abnormalities are good guideposts when hunting for cancer-related genes. We analyzed copy number alterations of 163 primary gastric cancers using array-based comparative genomic hybridization and simultaneously performed a genome-wide integrated analysis of copy number and gene expression using microarray data for 58 tumors. We showed that chromosome 6p21 amplification frequently occurred secondary to ERBB2 amplification, was associated with poorer prognosis and caused overexpression of half of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 44 publications
4
56
1
Order By: Relevance
“…This is supported by observations in malignant melanoma, for example, where GLO1 copy number increase has low prevalence (2%) in early stages and high prevalence (80 -89%) in advanced stages [68,72,73]. Recent studies have found very high prevalence of GLO1 copy number increase also in gastric cancer (33%) [74] and in "triple negative" breast cancer lacking expression of oestrogen and progesterone receptors and epidermal growth factor receptor-2 genes (83%) [75]. These tumour types do not respond well to currently available chemotherapy; such tumours may be sensitive to permeable Glo1 inhibitor chemotherapy when available clinically [47].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This is supported by observations in malignant melanoma, for example, where GLO1 copy number increase has low prevalence (2%) in early stages and high prevalence (80 -89%) in advanced stages [68,72,73]. Recent studies have found very high prevalence of GLO1 copy number increase also in gastric cancer (33%) [74] and in "triple negative" breast cancer lacking expression of oestrogen and progesterone receptors and epidermal growth factor receptor-2 genes (83%) [75]. These tumour types do not respond well to currently available chemotherapy; such tumours may be sensitive to permeable Glo1 inhibitor chemotherapy when available clinically [47].…”
Section: Discussionsupporting
confidence: 62%
“…These tumour types do not respond well to currently available chemotherapy; such tumours may be sensitive to permeable Glo1 inhibitor chemotherapy when available clinically [47]. In gastric cancer increased GLO1 copy number was linked to Glo1 expression and was a negative survival factor [74]. GLO1 copy number alteration through dicarbonyl stress and/or hypoxia may contribute to the development of Glo1-linked MDR in cancer chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, detoxifying enzyme GLO1 is a potential therapeutic target of human gastric cancer79, it was inhibited by M1 (Luteolin), M2 (Quercetin) and M4 (Kaempferol) (in herbs Salvia miltiorrhiza; Alpinia Officinarum Rhizoma; Rhizoma Galangae and Lindera Aggregate ), therefore enhancing the therapeutic effect for GIDs by the synergistic effect in Sanhe Decoction. In addition, the nitric oxide synthase (NOS) family of enzymes synthesize NO in endothelial cells80, which augments the generation of reactive oxygen species by mitochondria, and thereby triggering mechanisms of cell survival or death81.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that high expression of GLO1 in gastric cancer promotes tumor cell growth and proliferation, and enhances transcriptional activities of NF-κB and AP-1 [20,21]. Since a positive correlation between the level of GLO1 in prostate cancer tissues and the rate of cell proliferation was found, we considered that GLO1 may represent a risk factor for the development and progression of prostate cancer [22].…”
Section: Role Of Gloi In Tumor Development and Progressionmentioning
confidence: 99%
“…Hyperactivation of AP-2α, E2F4 and Nrf2 has been identified in human tumors, which induces GLO1 overexpression [29,30]. The high expression of GLO1 enhances transcriptional activities of NF-κB and AP-1, and thus activates PI3K/Akt signaling for cell survival and proliferation [20,23]. Moreover, abnormal expression of GLO1 accelerates methylglyoxal metabolism, which in turn inhibits cell apoptosis.…”
Section: Regulatory Mechanisms Of Gloi In Tumor Cell Proliferation Anmentioning
confidence: 99%